1994
DOI: 10.1021/np50104a010
|View full text |Cite
|
Sign up to set email alerts
|

A New Scalarane Sesterterpenoid from the Marine Sponge Cacospongia mollior

Abstract: A new sesterterpene, 12-deacetoxyscalaradial [2a] has been isolated from the sponge Cacospongia mollior, together with the previously described scalaradial [2b] and furoscalarol [3]. The structure of the new compound, proposed by spectral data, was confirmed by X-ray diffraction analysis. Compound 2a is the first scalarane sesterterpenoid, without a substituent at C-12, to have been identified in nature. It shows high antifeedant activity and is hot to taste for the human tongue. Both 2a and 2b display cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…The presence of four axial isooriented methyl groups in the tetracyclic system gives rise to distortions in the skeletal geometry similar to those observed in other molecules with analogous sequences of axial substituents (Mattia, Mazzarella, Puliti, Riccio & Minale, 1988;Croft, Ghisalberti, Skelton & White, 1983). In particular, the lengthening of C--C bond distances within the central core of the molecule, from atoms C4 to C18, and the widening of angles C4--C5--C10, C8--C9--C10 and C8--C14--C13 (Table 2) are similar to those found in 12-deacetoxyscalaradial (De Rosa et al, 1994).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The presence of four axial isooriented methyl groups in the tetracyclic system gives rise to distortions in the skeletal geometry similar to those observed in other molecules with analogous sequences of axial substituents (Mattia, Mazzarella, Puliti, Riccio & Minale, 1988;Croft, Ghisalberti, Skelton & White, 1983). In particular, the lengthening of C--C bond distances within the central core of the molecule, from atoms C4 to C18, and the widening of angles C4--C5--C10, C8--C9--C10 and C8--C14--C13 (Table 2) are similar to those found in 12-deacetoxyscalaradial (De Rosa et al, 1994).…”
supporting
confidence: 68%
“…These sesterterpenes have an important ecological role in preventing predation, as they develop an antifeedant effect in fish. For comparison with the strictly correlated 12-deacetoxyscalaradial (De Rosa et al, 1994) and similar molecules, we have performed the X-ray analysis of scalaradial, the main metabolite from the sponge C. mollior. Scalaradial, (I), first studied by Cimino, De Stefano & Minale (1974), is a tetracyclic scalarane-type sesterterpene which has two vicinal aldehydic functions adjacent to an endocyclic unsaturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The acetoxy group might either affect the conformation of the nearby aldehyde group or alter the surface complementarity between scalaradial and its taste receptor's binding site. 16) Our finding that mioganal tasted milder than miogadial might have resulted from decreased permeability through the epithelium of the tongue owing to its tricyclic skeleton or from the presence of the 3-formyl-2-methlene-3-butenal structure rather than a 3-formyl-3-butenal moiety. Additional studies are necessary to confirm the structure-activity relationships between unsaturated dialdehydes and pungency, and to investigate the physiological function of mioganal.…”
Section: Distribution Of Mioganal In Different Varieties Of Myoga Plantsmentioning
confidence: 85%
“…15) However, 12-deacetoxyscalaradial, which has the same structure as scalaradial except for the acetoxy group, tastes hot. 16) De Rosa et al 16) have suggested that the bulky acetoxy substituent at C-12 of scalaradial might be responsible for the lack of pungency. The acetoxy group might either affect the conformation of the nearby aldehyde group or alter the surface complementarity between scalaradial and its taste receptor's binding site.…”
Section: Distribution Of Mioganal In Different Varieties Of Myoga Plantsmentioning
confidence: 99%